ANALISIS KOMPARASI IMPLEMENTASI KURIKULUM MERDEKA DAN KURIKULUM 2013 - Diana Rossa Martatiyana; Aprianti Derlis; Hasna Wulan Aviarizki; Rizky Roland Jurdil; Triasari Andayani; Otib Satibi Hidayat (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2023)
The Indonesian Education Curriculum was updated with the implementation of the Merdeka Curriculum, replacing the 2013 Curriculum. This study aimed to compare the implementation of the Independent Curriculum and the 2013 Curriculum. The research used the Library Studies method and analyzed scientific articles from the Google Scholar database. The findings indicate that both curricula are based on the goals of the National Education System, focusing on fostering students' spiritual, religious attitudes, intelligence, and noble character. However, the 2013 Curriculum emphasizes developing student competencies in cognitive, affective, and psychomotor aspects with a scientific approach, while the Merdeka Curriculum prioritizes character building through the Pancasila Student Profile Project (P5) and implements differentiated learning to cater to students' individual learning needs.